The training of indigenous pedagogues in alternance in Paraná: a contribution to interculturality and bilinguism - Marcos Gehrke; Marlene Lucia Siebert Sapelli; Rosangela Celia Faustino (Universidade Federal do Norte do Tocantins, 2019)
The aim of this paper is to present the constitutional process of the experience of indigenous educators development of the Central West State University (Guarapuava / PR), highlighting the arrival of indigenous demand at the University, the participatory construction of the Pedagogical Project of the Course (PPC) and the implementation of Alternation Pedagogy in indigenous higher education in Paraná. Through documentary and bibliographical research, the role of indigenous movements in the fight for the right of access to higher education in Paraná is explained in an intercultural and bilingual perspective, and the urgent need for training of educators to work at indigenous schools in the state. In the context of the process of creation of the course of Indigenous Pedagogy, with the Pedagogy of Alternation, we highlight the principles that support actions designed and performed collectively, present in the Pedagogical Project and in the execution of the Course. The results of the ongoing development process show a better participation of indigenous peoples in the decisions and organization of indigenous higher education, the establishment of an intercultural and bilingual curriculum, as well as the establishment of an Intercultural Degree in Teaching, composed only of indigenous students, which has led actions with autonomy and self-management.